Agricultural transformation societies as social economy entities and vectors of sustainable development - Gómez Santos, María (REVESCO. Revista de Estudios Cooperativos, 2022)
The Agrarian Transformation Societies (SAT) are associative formulas characterized by the simplicity of their constitution, the flexibility of their legal regime or the absence of a mandatory minimum capital. Formulas close to other more well-known typologies of the social economy, such as cooperatives, but which, depending on their statutory design, can become very distant structures. Having stated the above, the object of this work will focus on addressing three issues. The first is to offer a general overview of the SAT, from its origins to the present. Second, its legal qualification as an entity of the social economy will be analyzed, focusing on the problems raised around it (if, automatically, the SAT has to be classified as such). The third issue to be examined will be the connection between the EWS and the Sustainable Development Goals (SDGs) contemplated in the 2030 Agenda.